Private valuation of compensation stock options - Cueto, Diego C. (2018)
In recent years, risk-adjusted compensation packages with stock options have increase in popularity, volume, and scope. The objective of this paper is to document the divergence between the cost to the firm and the value to the employee of compensations stock options. Simulations reaching numerical examples beyond previous work that halted at theoretical approaches achieve this goal. The cost to the firm and the valuation for a diversified investor would coincide. However, the employee that receives stock options is bearing more firm-related risk that he would under a portfolio optimization strategy. Therefore, the undiversified employee assigns a lower value to the option. The results presented in this paper may help to better understand the preferences for certain types of options over others, from the firm’s and from the holder’s perspective.